Activity matters: Physical exercise and stress coping during the 2020 COVID-19 state of emergency - Popov, S.; Sokic, J.; Stupar, D. (Psihologija, 2021)
Recent studies have demonstrated that social isolation during the 2020 COVID-19 pandemic has significantly impacted the mental and physical health of people worldwide.However, it remainsunknown whether physical activity can improve mental health in astate of emergency.The present study aimed to examine the importance of physical exercising and stress management mechanisms Recent studies have demonstrated that social isolation during the 2020 COVID-19 pandemic has significantly impacted the mental and physical health of people worldwide. However, it remainsunknown whether physical activity can improve mental health in astate of emergency.The present study aimed to examine the importance of physical exercising and stress management mechanisms